Subtrochanteric fracture in a Chinese woman with Paget's disease of bone and on long term bisphosphonate therapy: could it be An insufficiency fracture? - Lee, C.K.; Jeremy, P.; Simmrat, S.; Azura, M. (2011)
Paget's disease is common in Western countries but is very rare in Chinese populations. Although bisphosphonate has been widely used to treat symptomatic Paget's disease, prolonged use may be associated with insufficiency fracture. We highlight this rare case of Paget's disease in a Chinese lady who presented with an insufficiency fracture following long-term use of bisphosphonate.